HUBUNGAN DISMENOREA DENGAN AKTIVITAS BELAJAR PADA REMAJA - Nofeni , Rahkita Settia; Haniyah , Siti; Hikmanti , Arlyana (Universitas Pesantren Tinggi Darul Ulum, 2023)
Lower abdominal pain before or during menstruation is known as dysmenorrhea. Pain during menstruation has an impact on daily activities, especially learning activities in adolescents. The purpose of this study was to determine the relationship between dysmenorrhea and learning activities in adolescents at the Women’s Orphanage Muhammadiyah Purwokerto. This type of quantitative research and cross sectional research design is the method of this research. All adolescents in the orphanage are the population in this study. The sampling technique used total sampling and obtained as many as 32 adolescent. Data collection was taken using a pain degree questionnaire (Visual Analog Scale) and a learning activity questionnaire. The results of this study were as many as 24 adolescents (75%) had dysmenorrhea and 8 adolescents (25%) did not experience dysmenorrhea which included 17 adolescents (53.1%) whose learning activities were disrupted and 15 adolescents (46.9%) whose learning activities were not disturbed, while the results of data analysis using Spearman's rank correlation p <0.05 (0.000) and the closeness of the relationship is 0.660** (strong relationship). Thus this study has the conclusion that there is a relationship between dysmenorrhea and learning activities in adolescents at the Women’s Orphanage Muhammadiyah Purwokerto. Keywords: Dysmenorrhea, Learning activities, Adolescents